Experience of Frontline Nurse Working in Hospital-Based Settings During the COVID-19 Pandemic - Muhammad, Buyung Reza; Wardaningsih, Shanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the experiences of frontline nurses in dealing with COVID-19 patients during the pandemic. This research method uses a scoping review method with a search method on four journal databases consisting of Sage, PubMed, Science Direct, and Proquest. The results obtained were 424 articles were found in the journal database but only 9 articles met the criteria and were included in this study. Qualitative research data show that nurses experience psychological, social, and emotional stress. However, nurses can prepare coping strategies using self-care, distraction, and peer and family support. In conclusion, nurses in charge of caring for COVID-19 patients have serious challenges in maintaining individual coping with negative psychological and social responses. Therefore, it is important to strengthen government support and policies to improve nurses' welfare. Keywords: COVID-19, Qualitative, Experience, Frontline Nurse